Crashworthiness characteristic of aluminum/composite hybrid tubes under axial compression - Wirawan, Willy Artha; Sabitah, Ayan; Sakti, Gunawan; Harianto, Bambang Bagus; Agus Choiron, Moch.; Ilyas, R.A.; Sapuan, S.M.; Prasetijo, Joewono (Elsevier B.V., 2025)
This study investigates the crashworthiness performance and energy absorption characteristics of circular aluminum-composite hybrid tubes reinforced with layers of waru bark fiber. Four tube configurations were fabricated: Aluminum Circular Tube (ACT), Composite Circular Tube (CCT), Hybrid Inner Circular Tube (HICT), and Hybrid Outer Circular Tube (HOCT). These tubes were subjected to quasi-static axial compression loading tests. The reinforcement layers, oriented at 0°–90°, were bonded using epoxy resin. The experimental results revealed that the addition of reinforcement layers introduced new progressive crushing behaviors, such as internal curling and corkscrew patterns, which effectively mitigated buckling failure. The hybrid designs significantly enhanced energy absorption, with HOCT and HICT achieving improvements of 49.18% and 43.78%, respectively, compared to the unreinforced ACT. Among the configurations, HOCT demonstrated the highest crashworthiness, with a peak crushing force (IPFC) of 42.36 kN, a mean force (MF) of 24.66 kN, and a crush force efficiency (CFE) of 0.49%. However, the specific energy absorption (SEA) decreased as tube diameter and reinforcement density increased. These results offer valuable insights into the optimization of reinforced composite tube designs, highlighting their potential for advanced crashworthiness and energy absorption applications.